An Experience Of Executing Value Added Tax (Vat) In Pokhara - Sharma, Devilal (Janapriya Journal of Interdisciplinary Studies, 2017)
Indirect taxes have a dominant role in the whole tax structure of developing countries like Nepal. VAT has been in operation for the last Eighteen years; still it is facing a number of challenges owing to poor administration, lack of good faith and honesty, rampant corruption, political instability, the problems of non-issuance of bill, narrow coverage, etc. For the improvement in effective VAT implementation, various areas including proper billing system, efficient tax administration, intensive billing enforcement, wide coverage, computerization, etc. VAT registrants are involving in VAT fraud. In this situation IRD has the various challenges to control the VAT evasion and implement the policy in effective and efficient way. The study is focused on the effectiveness of the VAT implementation of VAT collection policy in real field. Hence, its main objective is to analyze the effectiveness of the VAT implementation. For efficient implementation VAT officials have to perform effectively. The IRO Pokhara is working hard to collect more and more VAT so far as possible from its working area. Many taxpayer educations program in different places and compulsorily registration campaign to VAT program have been organized by IRO, Pokhara. The effectiveness of IRO, Pokhara and its officials seemed as satisfactory. With regard to fairness, friendliness with VAT registrants and overall effectiveness is at satisfactory level. Most of registrants are satisfied with the administrative mechanism of VAT in Nepal as well as with the availability of VAT document and information and its clarity. But in case of getting VAT refund in cash VAT registrant are not satisfied. Except in case of VAT refund in cash most satisfaction level of VAT registrants toward present VAT collection policy and practice seems to be at a satisfactory level. The market monitoring and investigation is the main tool that IRO, Pokhara is applying to control the VAT evasion. Similarly taxpayer education, current year audit and tax audit, billing enforcement, and e-base tax system are the other the major tools and techniques obtained by IRD to control the VAT evasion. Janapriya Journal of Interdisciplinary Studies, Vol. III (December 2014), page: 34-46